The Effect of Attractiveness, Accessibility, and Halal Attributes on Return Interest in Religious Tourism at the 99 Dome Mosque in Makassar with Visitor Satisfaction as an Intervening Variable - Riska Amalia M.; Misbahuddin Misbahuddin; Irwan Misbach (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of attractiveness, accessibility, and halal attributes on satisfaction and revisit intention at the 99 Kubah Mosque in Makassar, using the Theory of Marketing Management (TMM), Tourism Marketing Theory, and Halal Tourism Marketing Theory approaches. The results showed that attractiveness (path coefficient 0.201, p-value 0.009) and accessibility (path coefficient 0.222, p-value 0.008) have a significant influence on visitor satisfaction. Halal attributes have a stronger influence on satisfaction (path coefficient 0.351, p-value 0.000). However, accessibility and halal attributes do not have a significant effect on revisit intention. Satisfaction is proven to strengthen the influence of attractiveness on revisit intention (path coefficient 0.722, p-value 0.000). This study confirms that satisfaction is the most dominant factor in encouraging revisit intention, while attractiveness and halal attributes play an important role in increasing visitor satisfaction. Therefore, managing attractions and fulfilling halal attributes is very important in enhancing the visitor experience, which ultimately influences the intention to return.